The Culture of Professional Self-Realization as a Fundamental Factor of Students' Internet Communication in the Modern Educational Environment of Higher Education - Maria Odinokaya; Tatyana Krepkaia; Oksana Sheredekina; Maya Bernavskaya (MDPI AG, 2019)
This article deals with the problem of the culture of professional self-realization of Russian students in the process of university education at the present stage. The role of information and communications technologies is revealed, in particular the interactive technology of self-regulation developed by the authors, as a necessary pedagogical condition for the successful professional self-realization of students. The paper describes the interactive technology of self-regulation formation used in teaching a foreign language in order to improve the educational process. The paper provides an analysis of the current state of the classroom educational environment in teaching a foreign language in order to determine the possibilities of improving the educational process. The main goal of the interactive technology of self-regulation formation is to optimize and intensify the activities of students in the classroom and extracurricular activities. The interactive technology of self-regulation formation in a nonlinguistic university was applied in the proposed work. Special attention was paid to the problem of structuring and the algorithmization of independent work. Ways for increasing interactivity are revealed, and an algorithm for teaching and speech actions in interactive mode was developed. It was established that the introduction of structured algorithmization using the interactive technology of self-regulation formation could be effectively used for teaching poorly prepared students. It has been established that the culture of professional self-actualization for modern students is directly dependent on the quality of online interaction with a university teacher. It was revealed that it is the student’s awareness of the objectives of learning interaction and ways for its implementation that allow him to competently perform his academic work, which in turn contributes to the actualization of personal professional qualities that are required by a university graduate for successful implementation in the future.